Eficácia de estratégia educativa para adesão ao tratamento anti-hipertensivo: programa MeTTA - Oliveira, Andressa Suelly Saturnino de (2017)
Aimed to test the effectiveness of an educational program of mobile text messaging for adherence to antihypertensive treatment. A randomized, controlled clinical trial with recruitment (n=344) conducted at the Integrated Diabetes and Hypertension Center, located in Fortaleza, Ceará. There was randomization between two groups, with 172 participants in each, allocated with equal sex ratio and time of diagnosis of hypertension. Control group (CG) was defined as the group that was composed of participants who received the usual assistance offered at the data collection site. The intervention group (IG) was composed of participants who received, for three months (April to June 2016), in addition to the usual assistance, text messages via mobile phone on adherence to antihypertensive treatment. The messages were specific to the difficulty indicated by the participant to adhere to the treatment: taking medications in accordance with the prescription; Reduced consumption of sodium and unhealthy foods; Practice of physical exercises. At the end of each month, IG participants received a telephone call. This intervention was called MeTTA Program. The outcome was adherence to the antihypertensive treatment, measured by means of the Questionnaire for Adherence to the Treatment of Systemic Hypertension (QATHAS). This instrument allows to obtain the final coefficient of adhesion, which can vary from 60 to 110. Adhesion was measured in both groups, before (baseline) and after the intervention period. Continuous variables were submitted to the Kolmogorov-Smirnov test for distribution analysis. To evaluate the associations between the groups, the chi-square test (or likelihood ratio) was used for the qualitative variables. For the quantitative, the Mann-Whitney U test was applied to the binary variables. For the comparison of intra-group adhesion averages before and after the intervention, the Wilcoxon test was used. The guidelines contained in Resolution Nº 466/2012 of the National Health Council for research involving human subjects were followed at all stages of the research. The groups, on the baseline, were homogeneous for all characteristics tested. With the losses, the final sample of the research was of 253 participants, being 112 of the CG and 141 of the IG. In CG, adherence (outcome) remained similar after the intervention (p=0,109). The level of adhesion at both times was 80 according to the scale. In the intra IG analysis, a significant difference was found between the means of the QATHAS coefficients (p<0,001). Adherence (outcome), after the intervention, was better: one level increase in the adherence scale: from 80 to 90. Regarding the postintervention period, the means of the QATHAS coefficients between CG and IG were compared. The mean of the QATHAS coefficients of the IG was higher than the CG (p<0,001). It was concluded that MeTTA Program was effective to motivate people, accompanied in an institution of secondary health care in Fortaleza, to adhere to antihypertensive treatment. He was able to increase the membership rank in QATHAS by one level.